Measurement of the topological branching fractions of the τ lepton at LEP - Dova, María Teresa (2001)
Using data collected with the L3 detector at LEP from 1992 to 1995 on the Z peak, we determine the branching fractions of the τ lepton into one, three and five charged particles to be: B(τ → (1-prong)) = 85.274 ± 0.105 ± 0.073%, B(τ → (3-prong)) = 14.556 ± 0.105 ± 0.076%, B(τ → (5-prong)) = 0.170 ± 0.022 ± 0.026%. The first uncertainties are statistical and the second systematic. The accuracy of these measurements alone is similar to that of the current world average.